PENGUATAN LITERASI MELALUI TAMAN BACA BERBASIS KEAGAMAAN PESANTREN DAN TEKNOLOGI - Iwan Kresna Setiadi; Yudi Nur Supriadi (Gapenas Publisher, 2021)
Literacy strengthening of Islamic Boarding School-based Reading Gardens and technology has become a conceptual reality that requires empirically to make it happen. Community Service Activities (PKM) provide real work empirical ideas for the advancement of better quality Islamic education. Literacy through reading gardens and pesantren-based technology can create institutional unity between pesantren and advances in science and technology. The value system and education system of Islamic boarding schools supported by technological literacy will answer balanced scientific challenges in the future. At this time the ability to read and write is the basic foundation for successful learning in the future. Departing from the real problems and conditions of the Daarul Musthofa Islamic Boarding School regarding literacy learning to strengthen the implementation of science and technology, it is necessary to make real efforts in providing solutions, through Community Service activities (PKM) UPN Veterans Jakarta through the development of reading partners, training, mentoring, and coaching that structured and comprehensive in the management of reading gardens and improving managerial quality. This activity is carried out to provide correct knowledge and practice about literacy learning. PKM is held as an empowerment process that intersects with the ability to create an Islamic boarding school environment that has the ability in several ways. This in turn makes the practice of community empowerment enter the area of ??the literacy movement. The presence of community empowerment in the literacy movement was moved to undergo a general transformation into a movement based on more specific issues, one of which was at Daarul Musthofa Islamic Boarding School as a forum for PKM activities. Efforts to strengthen literacy culture through reading gardens at Daarul Musthofa Islamic Boarding School have been carried out. This is marked by facilities that encourage the growth of students' interest in reading such as adequate chairs and tables, book collections, bookshelves, services, computers, and so on. (2) The reading garden at Daarul Musthofa Islamic Boarding School is effective in encouraging students' interest in reading, especially during recess. Turning off students, activities were held at the reading park such as visits to Gramedia, construction of reading gardens, book reviews, scientific papers, mapping, and other activities, which aim to encourage students to be more creative, innovative and produce works and have broad knowledge through reading gardens.